Effects of Tai Chi Training on Antioxidant Capacity in Pre- and Postmenopausal Women - Attakorn Palasuwan; Daroonwan Suksom; Irène Margaritis; Suphan Soogarun; Anne-Sophie Rousseau (Journal of Aging Research)
The risk of oxidative stress-related metabolic diseases increases with menopause and physical inactivity. We hypothesized that an 8-week Tai Chi (TC) training program (2 sessions in class; 2 sessions at home; 1-1:15/session) would improve antioxidant capacity and reduce cardiovascular risks in both pre- (n=8) and postmenopausal (n=7) sedentary women. Selected measures of physical fitness and blood parameters were analyzed before and after the program. Besides the well-known effects of TC on balance, flexibility, and maximum leg extensor strength, TC (1) increased erythrocyte glutathione peroxidase activity—an aerobic training-responsive antioxidant enzyme—and plasma total antioxidant status and (2) decreased plasma total homocysteine, a cardiovascular risk marker. In addition to being a low-velocity, low-impact, and relatively safe, TC is a suitable physical activity design for pre- and postmenopausal women to increase antioxidant defenses. Investigating breathing effects during TC movements would be an interesting area for further research in diseases prevention.